Hodnocení rizikových faktorů vzniku ROP, ocní vady a psychomotorický vývoj nedonosených detí v západoceském regionu, dvanáctileté sledování - Marková, A; Jurcuková, M; Dort, J; Huml, P; Dortová, E; Horáková, N (Ceska a slovenska oftalmologie, 2009)
OBJECTIVE: The retrospective study is focused on monitoring of risk factors necessary for retinopathy of prematurity genesis and monitoring children with retinopathy of prematurity and their ocular and psychomotoric morbidity. The study concerned children treated at the Faculty Hospital in Plzen (Pilsen, Czech Republic, E.U.). MATERIAL AND METHODS: Prematurely born children with ROP during the period 1. 1. 1994 - 31. 12. 2005 in Perinatological Centre in Plzen or in other 11 maternity clinics in West Bohemia were observed. Only surviving children with ROP diagnosis, gestation under 32 weeks and birth weight under 1500 grams were involved in the study. Children with ROP were divided into 2 groups according to the nation-wide methodic for early neonatological morbidity monitoring: 1) children with the low-grade ROP with spontaneous regression (1st and 2nd stage), 2) children with high-grade ROP (3rd - 5th stage) who underwent cryotherapy. Incidence of ROP was assessed in 3 categories based on the birth weight (500-749 g, 750-999 g, 1000-1499 g). Monitored risk factors of ROP genesis: number of blood transfusions, duration of necessary oxygenoterapy period, duration of artificial ventilation period, septicemia, and intraventricular bleeding. Incidence of myopia, anisometropia, strabismus, glaucoma, congenital cataract, and the retina condition were assessed in children with ROP. The General Practitioners' reports were used for observing the children's psychomotoric development. Children's school grades and enlistment to special schools were also observed. RESULTS: Eight hundred seventy children with the birth weight under 1500 g were born in West Bohemia in the referenced period and 702 of them were released home. The ROP was found in 63 living children, 40 of them with low-grade retinopathy (63.5%) and 23 of them with high-grade retinopathy (36.5%). The incidence of all stages of ROP in all living newborns with the very low birth weight in our region was 9.0% including 3.3% of high-grade ROP. The incidence of all stages of ROP in all living newborns in individual categories according to the birth weight was 40.3%, 16.0% and 2.1%, including 17.9%, 6.1% and 0.2% of the high-grade ROP respectively. The number of blood transfusions, duration of the artificial ventilation period, and septicemia are statistically very important risk factors. The duration of oxygenotherapy period is also important while intraventricular bleeding is just below the level of statistical significance. Fifty children out of 63 came for ophthalmologic examination. Only a single kid out of 50 children examined by ophthalmologist suffers from bilateral blindness (2%), 20 children suffer from myopia (40%), 18 from anisometropia (36%), 15 from strabismus (30%), and 2 from glaucoma (4%). Congenital cataract was diagnosed in none of them. Thirty-three children are scholars, 3 of them visit school for visually handicapped children, and 6 of them visit special schools. CONCLUSION: The number of prematurely born children is still slowly increasing. Despite this fact, the incidence of ROP in West Bohemia is decreasing thanks to the improving quality of neonatological care. The aim of ophthalmologists is to reveal ocular diseases as soon as possible and apply appropriate treatment.
Keywords: Developmental Disabilities; Infant, Newborn; hyperkinetická porucha; mozková obrna; Retinopathy of Prematurity; retinopatie nedonošených; Humans; novorozenec; Eye Diseases; lidé; novorozenec nedonošený; vývojové poruchy u dětí; Attention Deficit Disorder with Hyperactivity; rizikové faktory; Infant, Premature; oční nemoci; Cerebral Palsy; novorozenec s velmi nízkou porodní hmotností; Risk Factors; Infant, Very Low Birth Weight